Bioactivity and metabolomics changes of plant-based drink fermented by Bacillus coagulans VHProbi C08. (15th February 2022) - Shudong, Peng; Guo, Chaoqun; Wu, Songjie; Cui, Hongchang; Suo, Huayi; Duan, Zhi
Abstract: The purpose of this paper was to evaluate the potential of plant-based drink based on soy protein and fructooligosaccharide in the development of probiotic beverages after fermentation by Bacillus coagulans VHProbi C08. B. coagulans VHProbi C08 was isolated from sour cabbage, and the sporulation rate was 90.03%. After being treated at 95 °C for 15 min, the survival rate was 6.86 log CFU/mL. The whole gene of VHProbi C08 contains only one chromosome, 4123 protein-coding genes are predicted, and 824 genes are unique. Plant-based drink fermented by VHProbi C08 showed the highest antibacterial activity against B. cereus ATCC 14579, followed by S. aureus ATCC 29213, L. monocytogenes ATCC 19115, S. enteritidis ATCC 14028, V. parahaemolyticus ATCC 17802, and E. coli ATCC 25922. Its DPPH radical scavenging activity, hydroxyl radical scavenging activity and anti-lipid peroxidation activity were 0.39, 0.25 and 0.35 mmol Trolox/L, respectively. After UPLC-MS/MS detection and analysis; 17 major metabolites with significant changes in fermented and unfermented plant-based drink were identified, including 2-Hydroxycinnamic acid, d -Glucarate, L-Tryptophan, Deoxycytidine, Imidazole propionic acid, Hypoxanthine, etc. In addition, the properties of plant-based drink fermented by VHProbi C08 was relatively stable during storage. Highlights: A new thermostable Bacillus coagulans VHProbi C08 was screened. Gene size of VHProbi C08 is 3, 666, 784 bp, containing 4123 coding genes. Plant-based drink fermented by VHProbi C08 has great antibacterial and antioxidant activities. Significant changes of 17 substances in fermented plant-based drink. The properties of fermented plant-based drink were stable during storage.